Evaluation of the incidence of leaf rust and straw rust in oat interspecific crossings - Mariot, Márcio Paim; Sereno, Maria Jane Cruz de Melo; Federizzi, Luiz Carlos; Carvalho, Fernando Irajá Félix de (Pesquisa Agropecuaria Brasileira, 1998)
The wild species Avena sterilis L. has been employed for crossing with Avena sativa L. cultivars in order to increase the genetic variability and to transfer the important agronomic characteristics, mainly the resistance to leaf rust (Puccinia coronata avenae) and to stem rust (Puccinia graminis avenae). An experiment was conducted at the Agronomic Experimental Station from UFRGS, to evaluate the natural incidence of these diseases in the field in cultivated oat cultivars (UFRGS-7, UFRGS-8 and UPF-7), in wild introductions of Avena sterilis (I-377, I-378 and I-ARG) and in segregative generations from interspecific crossing in the purpose of verifying the possibility of transferring this wild genotype character for the cultivated ones. Genes for resistance, mainly to leaf rust, were transferred from wild genotypes I-377 and I-378 to Avena sativa. The possibility of transgressive segregation for resistance in some crossings was also evidenced.
Keywords: Avena sativa; Avena sterilis; disease; genetic breeding